A study on the factor that influence teachers at secondary level in using information technology in their teaching and its relationship with their job satisfaction / Rafikawati Rohani - Rohani, Rafikawati (2003)
Use of information technology in teaching process is important nowadays. By use of information technology, it may increase teachers' satisfaction towards their work. Therefore, these studies are examines the factors that will influence teachers in using IT and their relationship with their job satisfaction. A sample of 50 teachers in SMK Dato' Haji Mohd Redza Seremban Negeri Sembilan was given the questionnaire. The studies try to find the factor influence teachers using IT and relationship with motivation, job satisfaction, facilities available and other variables. Instead of self-administered questionnaires, other methods of research that have been used in this study are data collection and Statical Package for Social Science (SPSS). The finding is hopefully can contribute and help this school in order to plan activities increasing teachers’ perceptions towards Information Technology.